Tradisi Pamali Sebagai Media Pendidikan Karakter Berbasis Nilai Islam dalam Pengasuhan Anak Masyarakat Banjar - Norsyifa Norsyifa; Sarifah Sarifah; Sofiah Rahmi; Wafiq Norazizah (Madrasah: Jurnal Pendidikan Madrasah, 2026)
This study aims to understand how the pamali tradition in Banjar culture influences parental child-rearing practices. The research method employed is descriptive qualitative, with data collected through observation, in-depth interviews, and documentation. The formal object of this study is child-rearing practices within Banjar families, while the material object is the pamali tradition as a local value system passed down through generations. The scope of this study focuses on the Banjar community in the Amuntai region of South Kalimantan. The results indicate that pamali plays a significant role in instilling values of politeness, discipline, and social responsibility in children through symbolic and educational means. This tradition serves as a mechanism of social control that maintains the family’s moral balance. However, the excessive application of pamali can instill fear and limit children’s freedom of thought if not accompanied by rational explanations from parents. This study concludes that pamali holds high educational value when applied wisely and adapted to the changing times. The values it embodies can serve as a foundation for strengthening character education for children based on local wisdom within the Banjar community.